Energy‐efficient fuzzy logic‐based cross‐layer hierarchical routing protocol for wireless Internet‐of‐Things sensor networks. (10th April 2021) - Nasri, Mohsen; Helali, Abdelhamid; Maaref, Hassen
Summary: With rapid increase of the advancement in wireless technologies, the world is now moving toward smart wireless devices which require the communication and collaboration of the Internet of Things (IoT). The smart devices, which called sensor nodes, enhance the use of the IoT as the essential components of today's smart world. Therefore, the wireless sensor network (WSN) is the most widely used technology enabling IoT scenarios. Using the technology, a huge volume of data needs to be tackled and transmitted carefully via the internet. Since the lifetime of the network is related to the reduced battery capacity of the connected wireless sensor nodes, extending the network lifetime is the main goal to be achieved. Clustering algorithm has a significant effect on the system lifetime for the IoT‐enabled WSN applications. In this paper, a fuzzy‐based routing protocol (FRP‐LEACH) and a cross‐layer routing protocol (CLRP‐LEACH) are proposed based on the clustering topology. The proposed algorithms are designed for the healthcare IoT applications. These algorithms offer several advanced cloud‐based services and facilities to serve patients more effectually and protect the medical and paramedical framework from pandemic illness like the ongoing COVID‐19 pandemic. To address the above‐mentioned concerns, an energy efficient routing protocol based on fuzzy logic is proposed to optimize wireless Internet‐of‐Things sensor networks performance. Simulation results are presented, and they show that the proposed algorithms outperform current cluster based‐routing protocols using a fuzzy logic algorithm in terms of generating stable clusters and extending the network lifetime. Abstract : In this paper, the FRP‐LEACH and the CLRP‐LEACH algorithms have been proposed based on the clustering topology. The proposed algorithms are designed for IoT healthcare applications. These algorithms offer several advanced cloud‐based services and facilities to serve patients more effectually and protect the medical and paramedical framework from the ongoing COVID‐19 pandemic.